The Effect of Demographic Factors on The Investment Decision in Beef Cattle Farming Using Profit Sharing Systems in West Sumatera - I. Iskandar; Fitrimawati Fitrimawati (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2019)
The aim of this study was analyzing the demographic profile and its influence on investor’s investment decisions on the business of people’s cattle farm through benefit sharing system. The research was the survey method and data obtained from questionnaires by investors in cattle farming through benefit sharing system in West Sumatera. The method of data analysis was a multiple regression method with a variable dummy. The results of the study showed that the investors were from different age and sex. There were respondents who were young to old and the total numbers of woman and man were almost the same. Most of them are an entrepreneur and there are only a few of them who are civil servants or private sector worker. Their education starts from elementary school to college, but most of them are elementary school graduates. Education is crucial in investment decisions rather than gender, age, and occupation. These categories do not significantly affect investment decisions in benefit sharing system of beef farmers in West Sumatera.